Efektifitas Variasi Limbah Buah sebagai Atraktan pada Eco-Friendly Trap terhadap Jumlah Lalat dan Jenis Lalat yang Terperangkap - Siska Desti Rahayu; Agus Kharmayana Rubaya; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2020)
Flies are mechanical vectors of several types of diseases for human. In order to minimize the use of insecticide on flies, it is necessary to control them naturally and according to their density. The purpose of this study was to determine the effectiveness of the variation of fruit waste as an attractant in eco-friendly fly-trap for the number and types of flies trapped in Ambarketawang Central Market, Gamping, Sleman, DIY. The attractant used consisted of fruit waste of: orange (Citrus sinensis), mango (Mangifera indica), and watermelon (Citrullus vulgaris) with a weight of 55.35 gr. This study was a quasi-experiment with post-test only design with control group design. There were 6 replications at 3 measurement points. the research data were analysed with One Way Anova at a significance level of 0.05. The results showed that the average numbers of flies trapped in the eco-friendly flytrap were: 18 in orange (Citrus sinensis) waste; 20 in mango (Mangifera indica) waste; and 24 in watermelon (Citrullus vulgaris) waste. Based on the statis-tical test results, the obtained p value was <0.001, which shows that the difference in the above average numbers of trapped flies was statistically significant or show that the variation of fruit waste as attractant of eco-friendly fly-trap affects the number of trapped flies. Species of the trapped flies identified as house fly (Musca domestica) and green fly (Phenicia sp).